Sexual health norms and communication patterns within the close social networks of men who have sex with men and transgender women in Lima, Peru: a 2017 cross-sectional study - Ayer, Amrita (2021)
Background: Social networks, norms, and discussions about sexual health may inform sexual practices, influencing risk of human immunodeficiency virus (HIV) or sexually transmitted infection (STI) acquisition. To better understand social networks of Peruvian men who have sex with men (MSM) and transgender women (trans women), we examined key social network members (SNMs), participant perceptions of these network members’ opinions toward sexual health behaviors, and associations between network member characteristics and condomless anal intercourse (CAI). Methods: In a 2017 cross-sectional study, a convenience sample of 565 MSM and trans women with HIV-negative or unknown serostatus was asked to identify three close SNMs; describe discussions about HIV and STI prevention with each; and report perceived opinions of condom use, HIV/STI testing, and partner notification of STIs. Generalized estimating equations evaluated relationships between SNM characteristics, opinions, and discussions and participant-reported CAI. Results: Among participants who identified as MSM, 42.3% of key SNMs were perceived to identify as gay. MSM “never” discussed HIV and STI prevention concerns with 42.4% of heterosexual SNMs, but discussed them “at least once weekly” with 16.9 and 16.6% of gay- and bisexual- identifying SNMs, respectively. Among participants who identified as trans women, 28.2% of key SNMs were perceived as heterosexual; 25.9%, as bisexual; 24.7%, as transgender; and 21.2%, as gay. Trans women discussed HIV/STI prevention least with cis-gender heterosexual network members (40.2% “never”) and most with transgender network members (27.1% “at least once weekly”). Participants perceived most of their close social network to be completely in favor of condom use (71.2% MSM SNMs, 61.5% trans women SNMs) and HIV/STI testing (73.1% MSM SNMs, 75.6% trans women SNMs), but described less support for partner STI notification (33.4% MSM SNMs, 37.4% trans women SNMs). Most participants reported CAI with at least one of their past three sexual partners (77.5% MSM, 62.8% trans women). SNM characteristics were not significantly associated with participant-reported frequency of CAI. Conclusions: Findings compare social support, perceived social norms, and discussion patterns of Peruvian MSM and trans women, offering insight into social contexts and sexual behaviors. Trial registration: The parent study from which this analysis was derived was registered at ClinicalTrials.gov (Identifier: NCT03010020) on January 4, 2017.